Study of the Sensitivity of the LUX-ZEPLIN Detector to the Double Electron Capture Decay of Xe-124 - Castanheira, Susana Raquel Fonseca (2021)
Dissertação de Mestrado em Física apresentada à Faculdade de Ciências e Tecnologia